Possible Gamification Learning for Optimizing Student Learning Motivation? - Usep Sholahudin; Yenti Yenti (PT ARRUS Intelektual Indonesia, 2022)
With low student learning motivation, a teacher must be creative so that students can have a more optimal learning motivation than before. One way to optimize student motivation is to use Gamification Learning. Gamification is a process that aims to change non-game contexts, one of which is in teaching and learning activities to be more attractive by integrating game mechanics, aesthetics, and thinking to motivate students in the learning process. Gamification includes game design elements, including points, scoreboards, badges, and challenges. This study uses a literature review research method that collects data from journals, books, and several other scientific sources relevant to this research topic. The results obtained are Gamification Learning can optimize students learning motivation.